The scope of obligatory civil liability insurance of entities conducting medical activities and liability for damages resulting from violations of patients’ rights in the Polish law - Augustynowicz, Anna; Strzelec, Paweł; Wrześniewska-Wal, Iwona; Bobiński, Krzysztof; Kowalska, Mariola; Partyka, Olga; Czerw, Aleksandra Izabela (Journal of Education, Health and Sport, 2018)
Abstract: In the elaboration, the objective scope of obligatory civil liability insurance of entities conducting medical activities in the context of protection from damages resulting from violations of patients’ rights was presented. Based on art. 25 sec. 1 of the Act on Medical Activity, insurance protection covers damages that are the result of the provision of medical services or an illegal omission to provide them. It concerns consequences of erroneous actions related to the provision of medical services as well as damages occurring as a result of an unjustified refusal to provide a medical service or premature cessation of the provision of services if there was an objective prerequisite to continue them driven by medical grounds. The objective scope of insurance protection resulting from obligatory civil liability insurance of an entity conducting medical activities does not apply – as a rule – to damages resulting from violations of patients’ rights. It cannot be considered that a damage related to violation of a patient’s right constitutes a consequence of the provision of medical services or an illegal omission of the provisions of medical services. Such damage is a consequence of a violation of the patient’s right. Financial consequences of patients’ claims resulting from violations of patients’ rights will be borne by entities conducting medical activities. If a patient requests a financial redress, its payment will not be made from the obligatory civil liability insurance policy. The violation of patient’s right to medical services constitutes the only exception.